PERAN LEMBAGA PERBATO DALAM MELAKSANAKAN UPACARA MANGOKAL HOLI PADA MASYARAKAT BATAK TOBA DI KELURAHAN TALANG MANDI KECAMATAN MANDAU KABUPATEN BENGKALIS - Nainggolan, Sutri Marice; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Kelurahan Talang Mandi Mandau Subdistrict, Bengkalis Regency with the problem that is (1) How is the role of Perbato Institution in carrying out the Mangokal Holi ceremony on Batak Toba society in Talang Mandi Village? (2) What are the factors influencing the role of Lembaga Perbato in carrying out the Mangokal Holi ceremony on Batak Toba society in Kelurahan Talang Mandi ?. The purpose of this research is to explain the role of Lembaga Perbato in performing the ceremony of Mangokal Holi to Batak Toba society in Talang Mandi Village and to know the factors influencing the role of Lembaga Perbato in conducting the Mangokal Holi ceremony in Toba Batak society in Talang Mandi Village. This research is a qualitative research, the subject of this research is the key informant who know or spark the idea of the Perbato Institute and also the Mangokal Holi ceremony such as Chairman of Customs, Management of the Institute of Perbato and Community Leaders. As for object in this research is taken by using purposive sampling technique where society which used as informant is those who know institution of Perbato and ceremony of Mangokal Holi. To collect research data using guide guides (guides) and documentation. The results of the study illustrate that the institution of Perbato is very instrumental in every before until after the ceremony Mangokal Holi implemented. In every arrangement of the event, the Institute of Perbato has a role in the intermediary of obtaining the excavation permit to the Social Service, leading the meeting, digging and retrieving the bones, receiving the offerings (somba-somba) in the form of food from the family conducting the ceremony. But there is still lack of in the institution in carrying out its role. In addition, there are factors that influence the role of the institution, namely the preparation of inadequate roles, the difficulty of role shifting, role conflict or role failure. Keywords: Mangokal Holi Ceremony, Perbato Institute, Role